Urban-Rural Differences in the Trends of Type 1 and Type 2 Diabetes Among Adults Who Received Medical Treatment from Public Hospitals in Resource-Poor Community Tigray, Ethiopia - Gebremedhin G (Dove Medical Press, 2020)
Getachew Gebremedhin,1,2 Fikre Enqueselassie,2 Negussie Deyessa,2 Helen Yifter3 1College of Medicine and Health Sciences, Department of Nursing, Adigrat University, Adigrat, Ethiopia; 2College Health Sciences, School of Public Health, Addis Ababa University, Addis Ababa, Ethiopia; 3College Health Sciences, School of Medicine, Addis Ababa University, Addis Ababa, Ethiopia†Fikre Enqueselassie passed away on October 28, 2019Correspondence: Getachew Gebremedhin Email guchosole786@gmail.comObjective: This study carried out to describe urban-rural differences in the trend of type 1 and type 2 diabetes among adults who have received medical treatment from public hospitals over the last five years.Methods: The trends of adult diabetes assessed from September 1, 2013, to August 31, 2018, using hospital-based retrospective medical records of 299,806 adult patients in the adult medical outpatient and emergency units. Data were collected using a uniform data abstraction format. An extended Mantel-Haenszel chi-square test of the linear trend used to examine the trend over time.Results: Of the total 299,806 adult patients, 3056 (1.02% (95% CI: 0.98– 1.06)) patients were confirmed diabetes patients. The overall trend in the proportion of diabetes had increased from 6.8 to 14.3 per 1000 adult patients. The trend of type 1 diabetes increased for both urban from 1.0 to 2.2 per 1000 adult urban residents and rural from 1.2 to 2.6 per 1000 adult rural residents, with statistically a significant increase (χ2= 9.1, P=0.002) and (χ2=17.8, P< 0.001) for linear trend, respectively. The trend of type 2 diabetes increased for both urban from 6.9 to 14.0 per 1000 adult urban residents and rural from 4.0 to 9.5 per 1000 adult rural residents, with a statistically significant increase (χ2=68.4, P< 0.001) and (χ2=74.2, P< 0.001) for linear trend, respectively. The higher increase in the proportion of both type 1 and type 2 diabetes observed among women patients.Conclusion: The trend in the proportion of type 1 and type 2 diabetes increasing for both urban and rural residents, with a higher increase observed among women. These findings highlight health-care professionals and policymakers to design effective public health policies to treat each type of disease.Keywords: urban, rural, trend, type 1 diabetes, type 2 diabetes